Impact of Ice Slurry Ingestion During Break-Times on Repeated-Sprint Exercise in the Heat - Naito, Takashi; Haramura, Miki; Muraishi, Koji; Yamazaki, Misa; Takahashi, Hideyuki (Sports Medicine International Open, 2020)
The study aimed to investigate the effects of ice slurry ingestion during break times and half-time (HT) on repeated-sprint performance and core temperature in the heat. Seven males performed two different trials as follows: ice slurry (−1°C) or room temperature water ingestion at each break and HT break at 36.5°C, 50% relative humidity. Participants performed 30 sets of 1-min periods of repeated- sprint exercises protocol using a cycling ergometer. Each period consisted of 5 sec of maximal pedaling, 25 sec of pedaling with no workload, and 30 sec of rest; two sets of exercise periods were separated by 10 min of rest. Each break was implemented for 1 min after every 5 sets. The rectal temperature in ice slurry ingestion was significantly lower than that of the room temperature water at 45 set (p=0.04). Total and mean work done was greater in ice slurry ingestion compared to room temperature water ingestion (p < 0.05). These results suggested that ice slurry ingestion during break times and HT break may be an effective cooling strategy to attenuate the rise of core temperature in the second half of exercise and improve the repeated-sprint exercise capacity in the heat.
Keywords: cooling; rectal temperature; work done; forehead skin temperature; perceptual sensations